2009
DOI: 10.1038/aps.2009.98
|View full text |Cite
|
Sign up to set email alerts
|

High K+-induced contraction requires depolarization-induced Ca2+ release from internal stores in rat gut smooth muscle

Abstract: Aim: Depolarization-induced contraction of smooth muscle is thought to be mediated by Ca 2+ influx through voltage-gated L-type Ca 2+ channels. We describe a novel contraction mechanism that is independent of Ca 2+ entry. Methods: Pharmacological experiments were carried out on isolated rat gut longitudinal smooth muscle preparations, measuring isometric contraction strength upon high K + -induced depolarization. Results: Treatment with verapamil, which presumably leads to a conformational change in the channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…The 2 major types of voltage-gated potassium channels are the sustained delayed rectifier current and the transient A-type current. 86,87 The increased level of potassium can lead to depolarization of the cell membrane in smooth muscles, which is associated with the entry of extracellular calcium ions as well as stimulation of bowel contractions. It has been suggested that ryanodine and inositol triphosphate receptors are involved in depolarization-induced calcium currents in muscle cells.…”
Section: 81mentioning
confidence: 99%
“…The 2 major types of voltage-gated potassium channels are the sustained delayed rectifier current and the transient A-type current. 86,87 The increased level of potassium can lead to depolarization of the cell membrane in smooth muscles, which is associated with the entry of extracellular calcium ions as well as stimulation of bowel contractions. It has been suggested that ryanodine and inositol triphosphate receptors are involved in depolarization-induced calcium currents in muscle cells.…”
Section: 81mentioning
confidence: 99%
“…Before the start of the experiment, a stable baseline tone was achieved for at least 50 min. Under these conditions, both contractions and relaxations have been found to be very reproducible and to show low variance between different tissue specimens in previous studies [21,22] . Isometric contractions and relaxations of the smooth muscle strips induced by KCl or purinergic ligands were measured by force transducers (MLT0201, ADInstruments, Oxford, UK) and recorded with a bridge amplifier (ML224, ADInstruments) connected to an analog-to-digital converter (Powerlab 4/30, ADInstruments) and then analyzed by the Chart 5 software (ADInstruments).…”
Section: Isometric Contractions In Vitromentioning
confidence: 70%
“…The organ bath fluid was not corrected for osmolarity after the addition of KCl. However, the resulting increase in osmolarity was well tolerated by the preparations, and hyperosmotic control experiments with addition of the same amount of NaCl revealed relaxation of the smooth muscle rather than contraction [21] . Each gut preparation was tested with KCl for depolarization-induced contractions at the beginning and at the end of the experiment and was included in the study when the KCl-induced contraction at the end of the experiment was at least 50% of the initial response.…”
Section: Isometric Contractions In Vitromentioning
confidence: 93%
“…Activation of the muscarinic receptor induces activation of a G proteincoupled receptor which activates phospholipase-C to produce inositol-1,4,5, triphosphate (IP3) and diacylglycerol (DAG). These molecules mediate Ca 2+ release or entry into smooth muscle cells (Macara and Rico, 1992;Bolton et al, 1999;Kirschstein et al, 2009). Thus, citral and LE may block the production of IP3 and/ or block the release of Ca 2+ from the storage sites.…”
Section: Discussionmentioning
confidence: 99%
“…Substances that inhibit the K + -induced contraction are considered as blockers of Ca 2+ influx (Brankovic et al, 2009;Kirschstein et al, 2009).…”
Section: Discussionmentioning
confidence: 99%